Integrating Ecological Education in Social Science Learning at the Elementary School : A Case Study at SD Negeri Tegalrejo 2 Yogyakarta, Indonesia - Jayanti, Nourma; Pambudi, Dholina Inang; Masaei, Nazori (The Indonesian Institute of Science and Technology Research, 2023)
Environmental education can be integrated with the field of study in schools with interdisciplinary, multidisciplinary and transdisciplinary approaches, one of which is through social studies learning. The integration between environmental education and social studies learning is summarised by instilling awareness as citizens responsible for fellow human beings, the state and the natural surroundings and providing a broad insight into the importance of protecting the environment, which will impact all aspects of human life. This study aimed to describe the integration of environmental education in social science learning and find the supporting and inhibiting factors. The research used in this research is qualitative. Data collection techniques in this study were observation, interviews, and documentation. The validity of the data used in this study is technical triangulation. The data analysis technique uses the Miles and Huberman methods, which consist of information gathering, presentation, concluding, and data reduction. The results of this study are the implementation of integrating environmental education in social science learning for the upper class. Integrating ecological education in social science teaching for the upper class is done through the planning, implementation, and evaluation stages. The planning carried out includes planning learning objectives, learning materials, learning methods, learning media, and assessment of learning outcomes. Implementation occurs when learning takes place with the preliminary activity, core, and closing stages. Assessment is carried out by assessing students' cognitive, affective, and psychomotor domains. The supporting factors for its implementation are the availability of facilities and infrastructure, the teacher's understanding of linking social science learning material with environmental education, and the synergy of all school members, as well as the inhibiting factors for its implementation, namely the lack of teacher creativity in developing integrated learning indicators for environmental education in social science material and students who less active during the lesson.